Multicentre experience of home omalizumab treatment for chronic spontaneous urticaria. Issue 6 (15th July 2019) - Denman, Sarah; El-shanaway, Tariq; Carne, Emily; Devlin, Lisa; Savic, Sinisa
Abstract : Introduction: Due to perceived risk of anaphylaxis, home treatment with omalizumab has been limited. Within the UK, most centres administer omalizumab in a hospital setting. However, the reported prevalence of anaphylaxis is low and in December 2018 home treatment became licensed. A home treatment pathway was previously reported by one UK centre, and this update describes three UK centres' experience of home omalizumab treatment. Methods: The medical records of omalizumab patients were retrospectively reviewed. Results: A total of 137 adult patients have received home omalizumab treatment; home treatment duration 0–44 months. There was no increase in adverse effects seen in patients treated at home. There were no reported adherence issues and no reduction in efficacy. Patients report they prefer home treatment due to increased flexibility and reduced impact on daily life/work. Conclusion: Home treatment with omalizumab is a safe and effective alternative to hospital administration.